Control of Fusarium Wilt of Chili With Chitinolytic Bacteria - Dwi Suryanto; Siti Patotah; Erman Munir (HAYATI Journal of Biosciences, 2010)
Biological control of plant disease using antagonistic microorganism has been obtaining much attention and implemented for decades. One of the potential microorganisms used in this strategy is chitinolytic bacteria. Utilization of this bacteria ranges from cell life, enzymes, genes, or other metabolites. In this study, we examined the ability of chitinolytic bacteria as a biocontrol agent of Fusarium wilt of red chili (Capsicum annuum L.) seedlings. The ability of chitinolytic bacteria to suppress the disease was evaluated by soaking red chili seeds in the bacterial isolates solution for 30 minutes prior seedling. Percentage of seedling of treated chili seed at end of study (4-weeks) ranging from 46 to 82.14%. Relative reduction of the seedling damping-off was observed in all bacterial treatment ranged from 28.57 to 60.71%. Furthermore, manifestation of bacterial suppression to Fusarium wilt was also exhibited by increasing of seedling height (ranged from 7.33 to 7.87 cm compared to 6.88 cm) and dry-weight (ranged from 2.7 to 4.3 mg compared to 2.3 mg). However, no significant effect was observed in leaf number. Then, from all chitinolytic isolates tested, BK08 was the most potential candidate for biological control agent of Fusarium wilt in chili seedling.